2021
DOI: 10.21037/jgo-21-508
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and prognostic significance of ALOX12B and PACSIN1 expression in gastric cancer by genome-wide RNA expression and methylation analysis

Abstract: Background: Stomach adenocarcinoma (STAD) is one of the common gastrointestinal cancers, characterized by late discovery and metastasis. However, research of gene methylation and expression in gastric cancer (GC) metastasis has been quite limited. This study aimed to investigate the altered gene expression patterns between metastasis and non-metastasis samples using high-throughput RNA and methylation profiles from a large number of patients. Another aim was to identify a specific potential metastasis biomarke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
(48 reference statements)
1
3
0
Order By: Relevance
“…Moreover, high expression of PACSIN1 was associated with advanced stages, lymph node metastasis and poor prognosis. These findings suggested that PACSIN1 may function as an oncogene in GC, which is in line with the findings of Liu et al [23]. PACSIN1, an autophagy regulator, promotes lysosomal fusion and autophagy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, high expression of PACSIN1 was associated with advanced stages, lymph node metastasis and poor prognosis. These findings suggested that PACSIN1 may function as an oncogene in GC, which is in line with the findings of Liu et al [23]. PACSIN1, an autophagy regulator, promotes lysosomal fusion and autophagy.…”
Section: Discussionsupporting
confidence: 91%
“…For instance, overexpressed PACSIN1 is associated with poor overall survival in luminal breast cancer patients [22]. Overexpressed PACSIN1 predicts the metastasis of GC [23]. However, the underlying molecular mechanisms are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has found a weak to moderate correlation between gene expression and DNA methylation, and it has only identified a small subset of genes that are highly controlled by DNA methylation. [29,30] The predictive value of JAM3 DNA methylation was also explored. Among GC patients, we discovered that a hypermethylated JAM3 gene was associated with better OS and progression-free survival.…”
Section: Discussionmentioning
confidence: 99%
“…The predictive characteristics of some gene expressions had great significance in the application of clinical prognosis and identification of biomarkers. Studies showed that compared with the STAD patients without metastasis, the expression levels of ALOX12B and PACSIN1 were higher in patients with tumor metastasis, and the survival rate of patients with high expression was significantly lower than that of patients without metastasis [ 8 ]. These two genes may be potential biomarkers of metastasis and poor prognosis, which provide more information for follow-up comprehensive treatment and diagnosis of GC.…”
Section: Introductionmentioning
confidence: 99%